Tariyxıy shınlıqtı imitaciyalawda muzey eksponatlarınıń áhmiyeti - Seyfullaev, A.S (SCIENCE and SOCIETY, 2023)
The article says that museums are of great importance in imitating historical reality, in developing historical knowledge and historical thinking through unique exhibits.
Keywords: historical reality; historical thinking; museum; imitation of museum expositions; museum pedagogy; virtual expedition; cultural education